An Fc–Small Molecule Conjugate for Targeted Inhibition of the Adenosine 2A Receptor. (26th August 2016) - Hsiao, Po‐Yuan; Kalin, Jay H.; Sun, Im‐Hong; Amin, Mohammed N.; Lo, Ying‐Chun; Chiang, Meng‐Jung; Giddens, John; Sysa‐Shah, Polina; Gabrielson, Kathleen; Wang, Lai‐Xi; Powell, Jonathan D.; Cole, Philip A.
Abstract: The adenosine A2A receptor (A2A R) is expressed in immune cells, as well as brain and heart tissue, and has been intensively studied as a therapeutic target for multiple disease indications. Inhibitors of the A2A R have the potential for stimulating immune response, which could be valuable for cancer immune surveillance and mounting a response against pathogens. One well‐established potent and selective small molecule A2A R antagonist, ZM‐241385 (ZM), has a short pharmacokinetic half‐life and the potential for systemic toxicity due to A2A R effects in the brain and the heart. In this study, we designed an analogue of ZM and tethered it to the Fc domain of the immunoglobulin IgG3 by using expressed protein ligation. The resulting protein–small molecule conjugate, Fc–ZM, retained high affinity for two Fc receptors: FcγRI and the neonatal Fc receptor, FcRn. In addition, Fc–ZM was a potent A2A R antagonist, as measured by a cell‐based cAMP assay. Cell‐based assays also revealed that Fc–ZM could stimulate interferon γ production in splenocytes in a fashion that was dependent on the presence of A2A R. We found that Fc–ZM, compared with the small molecule ZM, was a superior A2A R antagonist in mice, consistent with the possibility that Fc attachment can improve pharmacokinetic and/or pharmacodynamic properties of the small molecule. Abstract : Bigger is better : By using a semisynthetic approach, an Fc–small molecule conjugate, Fc–ZM, was developed for targeted inhibition of the adenosine 2A receptor (A2A R). Fc–ZM displayed superior pharmacologic properties compared to ZM alone and was able to functionally interact with A2A R and Fc receptors, present on lymphocytes and antigen‐presenting cells, respectively.